2020
DOI: 10.1136/annrheumdis-2020-eular.2059
|View full text |Cite
|
Sign up to set email alerts
|

Sat0151 efficacy and Safety of Upadacitinib Versus Abatacept in Patients With Active Rheumatoid Arthritis and Prior Inadequate Response or Intolerance to Biologic Disease-Modifying Anti-Rheumatic Drugs (Select-Choice): A Double-Blind, Randomized Controlled Phase 3 Trial

Abstract: Background:Upadacitinib (UPA) is an oral, reversible, selective JAK 1 inhibitor approved for the treatment of moderate to severe rheumatoid arthritis (RA). The efficacy/safety of UPA has been demonstrated in phase 3 studies, including superiority to adalimumab in patients (pts) with prior inadequate response (IR) to methotrexate.1-4Objectives:To assess the efficacy/safety of UPA vs abatacept (ABA) in pts with prior IR or intolerance to biologic DMARDs (bDMARDs).Methods:Pts were randomized to once daily UPA 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 0 publications
1
6
0
16
Order By: Relevance
“…4). While not included in this integrated analysis, the safety profile of upadacitinib reported in SELECT-CHOICE was consistent with that from the five pivotal trials, with no new risks identified [38].…”
Section: Summary Of Risksmentioning
confidence: 60%
See 2 more Smart Citations
“…4). While not included in this integrated analysis, the safety profile of upadacitinib reported in SELECT-CHOICE was consistent with that from the five pivotal trials, with no new risks identified [38].…”
Section: Summary Of Risksmentioning
confidence: 60%
“…2). Similarly, upadacitinib 15 mg demonstrated superior improvement in disease activity and remission compared with abatacept in bDMARD-IR patients [38].…”
Section: Summary Of Benefitsmentioning
confidence: 92%
See 1 more Smart Citation
“…Upadacitinib ha recentemente ottenuto dall’Agenzia Europea per i Medicinali ( European Medicines Agency , EMA) l’approvazione in Europa per diverse indicazioni, tra cui il trattamento dell’AR da moderata a grave in pazienti adulti che hanno avuto una risposta inadeguata o che sono intolleranti a uno o più farmaci antireumatici modificanti la malattia ( 24 ). L’efficacia e la sicurezza di upadacitinib sono state valutate in un ampio programma di studi clinici randomizzati ( 25 , 26 , 27 , 28 , 29 ), tra cui lo studio di fase III SELECT-CHOICE ( 30 , 31 ). In riferimento a quest’ultimo studio, l’efficacia e la sicurezza di upadacitinib sono state confrontate rispetto a quelle di abatacept ( 30 , 31 ).…”
Section: Introduzioneunclassified
“…Упадацитиниб -это пероральный селективный ингибитор JAK1 с удобной схемой приема -1 таблетка (15 мг) в сутки. Установлено, что упадацитиниб в дозе 15 мг не уступает по эффективности дозе 30 мг, но вызывает меньше нежелательных лекарственных реакций (НЛР) [4][5][6][7][8][9][10][11].…”
unclassified